Breeding goals for milk and meat producing sheep in Hungary - Kukovics S.; Molnar A.; Abraham M.; Javor A. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
There are 6,799 sheep farms in Hungary and 21 different breeds are bred. The breeding goals vary from farm to farm depending on the flock size, the available land and the main products (meat or meat and milk). On the small farms survival is the most important aim, while on the bigger ones there are possibilities to increase the meat and milk production. In general, there is a very big shortage of animals, the stocking rate is much lower than expected, so the basic breeding goal is to increase the number of sheep in the country.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)